O ADOECIMENTO DO PROFISSIONAL DOCENTE: a Síndrome de Burnout e suas implicações na vida profissional do professor (a) no município de Curralinho-PA - CORREA, Nino Castilho (2024)
The present work has as objective to diagnose if there is the presence of Burnout Syndrome in the teachers of the infantile education. Firstly, a theoretical research was carried out focusing on the definition of the pathology and the multiple difficulties in the school environment that can generate burnout. According to this reality, data were collected through the Maslach Burnout Inventory (MBI) questionnaire, delivered to two municipal schools, using samples of 10 teachers from each one. The methods used were systematic observation, interview, questionnaire, letter of presentation, orientation, informed consent form and preliminary questionnaire identifying Burnout Syndrome. According to the data collected and analyzed, it was verified the existence of the Syndrome, in the initial phase in 50% of the interviewed teachers of one of the samples. It was concluded that teachers need to have a better quality of work, because Burnout interferes significantly in the work environment, in the teacher- student relationship and in the health of the professional.